Clinical experiences of ICSI-ET thawing cycles with embryos cryopreserved at different developmental stages - Konc, Janos (Kluwer Academic Publishers-Plenum Publishers, 2005)
Purpose: The aim of our study was to analyze factors including survival, implantation and pregnancy rate, patients’ age and BMI, abortions and extra uterine pregnancies that might influence the outcome of ICSI-ET thawing cycles. Methods: A total of 147 cycles with embryos cryopreserved at different developmental stages were retrospectively evaluated. Results: No difference was found in the survival, implantation and pregnancy rates of embryos cryopreserved on Day 2–3 and 5. However, in the pregnant group significantly higher implantation rate was observed with Day 5 blastocysts then with Day 2 or 3 early embryos. We found no difference in the number of abortions and extra uterine pregnancies between fresh and frozen ICSI-ET cycles. Higher BMI was found in the pregnant than in the non-pregnant group. However, the age of patient had no effect on the results. Conclusions: Developmental stage of embryo and patients’ BMI influences the success of ICSI-ET thawing cycles.